FASHION ACCESSORIES FROM ANKARA WAX PRINTS IN NIGERIA - Adeoti, A. A.; Kalilu, R. O. R. (Art and Design, 2023)
The purpose of this study is to provide preliminary art history of the accessories made from Ankara fabrics and make a scholastic record of the production of the accessories with the use of Ankara wax print fabrics in Nigeria. The ephemerality nature of fabrics with creativity, innovation and the dearth of literary materials in this area of art make the study to be expedient. Methodology: this study adopts both descriptive and explanatory research designs to carry out the research with qualitative method in analyzing the data. The sources of data are from both primary and secondary sources making the data to be concise and effective. Result: the study identified that the cotton texture and colourful designs make the accessories to be easily produced without stress. Therefore, many accessories for fashion are produced daily showing African nature in day-to-day dressing. Scientific novelty: the study discovered the usefulness of African fabrics and wears which could be publicize rather than the imported fabrics and wears being widely used in Nigeria which will be of great value in Nigerian fashion system. Practical significance: the findings of this research reveal that Ankara wax prints transcends sewing the fabric into dress wears. Inspirations are increasing daily, and the fabric is becoming more popular in the market world. With the technology in place and the taste of the consumers dictate the kind of styles and accessories to be created for the users.